2022
DOI: 10.3389/fpubh.2022.900883
|View full text |Cite
|
Sign up to set email alerts
|

How to make more people adopt healthy behaviors? Assessing health literacy, health promoting lifestyle and their association of community residents in Shenzhen, China

Abstract: IntroductionHealth literacy (HL) has been concerned a key factor for determining the use of health information and promoting health. The study aimed to explore the relationship between different health literacy types and health promoting lifestyle (HPL) in different health literacy population.MethodsThe survey analyzed a sample of 16,921 community residents in Shenzhen. The Chinese Citizen Health Literacy Questionnaire and health-promoting lifestyle profile II (HPLP- II) were used to assess health literacy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This difference might be attributed to the fact that people living in Shenzhen are provided with fruitful medical resources and health information offerings from the high-quality primary healthcare system supported by the municipal government [ 22 ]. Additionally, evidence showed that health literacy was apparently higher among people in Shenzhen compared with the Chinese average level, which referred to the ability and basic diathesis to acquire and use health information and make health-associated associations, for example, vaccination in the present study [ 23 , 24 ]. Statistically significant influenza-associated factors in knowledge and attitude survey items were identified, which showed that people having sufficient and correct knowledge as well as positive attitude towards influenza vaccination were associated with having vaccination.…”
Section: Discussionmentioning
confidence: 72%
“…This difference might be attributed to the fact that people living in Shenzhen are provided with fruitful medical resources and health information offerings from the high-quality primary healthcare system supported by the municipal government [ 22 ]. Additionally, evidence showed that health literacy was apparently higher among people in Shenzhen compared with the Chinese average level, which referred to the ability and basic diathesis to acquire and use health information and make health-associated associations, for example, vaccination in the present study [ 23 , 24 ]. Statistically significant influenza-associated factors in knowledge and attitude survey items were identified, which showed that people having sufficient and correct knowledge as well as positive attitude towards influenza vaccination were associated with having vaccination.…”
Section: Discussionmentioning
confidence: 72%
“…In 89 relevant papers in HL, studies authored by Chinese scientists are the most prevalent, with 27 studies that surveyed HL levels in various groups of people. They were patients 22 -27 or general public, secondary, 28 -30 high school, 30,31 college students, 32,33 women, 34 12 years old and above, 16,15,35 -43 or older adults. 44 -47 Taiwan had the second-highest number of HL measurement articles, with 16 published papers.…”
Section: Resultsmentioning
confidence: 99%
“…No statistically significant association was observed between gender and nutritional risk in the results of the univariate analysis, although women showed a greater incidence of nutritional risk as in other studies. Highly educated older persons are more conscientious about health and are more capable of acquiring nutritional knowledge and taking an active role in developing healthy eating habits and nutritional behaviors [ 43 , 44 ]. Another study has shown that marital status is negatively associated with the nutritional status of older adults, in which those in the widowed or divorced group have lower nutritional status than those in the spoused group [ 45 ].…”
Section: Discussionmentioning
confidence: 99%